Lecture 6 PDF
Lecture 6 PDF
Lecture 6 PDF
∞
1
f Im ( t ) = ------
2π ∫–∞ [ FRe ( ω ) sin ωt + FIm ( ω ) cos ω t ] dω (8.35)
We observe that the integrand of (8.35) is zero since it is an odd function with respect to ω because
both products inside the brackets are odd functions*.
Therefore, f Im ( t ) = 0 , that is, f ( t ) is real.
We can state then, that a necessary and sufficient condition for f ( t ) to be real, is that F ( – ω ) = F∗ ( ω ) .
Also, if it is known that f ( t ) is real, the Inverse Fourier transform of (8.3) can be simplified as fol-
lows:
From (8.13),
∞
1
f Re ( t ) = ------
2π ∫–∞ [ FRe ( ω ) cos ωt –FIm ( ω ) sin ωt ] dω (8.36)
and since the integrand is an even function with respect to ω , we rewrite (8.36) as
∞
1
f Re ( t ) = 2 ------
2π ∫0 [ F Re ( ω ) cos ωt – F Im ( ω ) sin ωt ] dω
(8.37)
∞ ∞
1 1 j [ ωt + ϕ ( ω ) ]
= ---
π ∫0 A ( ω ) cos [ ωt + ϕ ( ω ) ] dω = --- Re
π ∫0 F ( ω )e dω
a1 f1 ( t ) + a2 f2 ( t ) + … + an fn ( t ) ⇔ a1 F1 ( ω ) + a2 F2 ( ω ) + … + an Fn ( ω ) (8.38)
Proof:
The proof is easily obtained from (8.1), that is, the definition of the Fourier transform. The proce-
dure is the same as for the linearity property of the Laplace transform in Chapter 2.
2. Symmetry
If F ( ω ) is the Fourier transform of f ( t ) , the symmetry property of the Fourier transform states that
F ( t ) ⇔ 2πf ( – ω ) (8.39)
that is, if in F ( ω ) , we replace ω with t , we get the Fourier transform pair of (8.39).
Proof:
Since
∞
1
∫–∞ F ( ω )e
jωt
f ( t ) = ------ dω
2π
then,
∞
– j ωt
2πf ( – t ) = ∫–∞ F ( ω )e dω
ω
f ( at ) ⇔ ----- F ⎛ ---- ⎞
1
a ⎝ a ⎠ (8.40)
that is, the time scaling property of the Fourier transform states that if we replace the variable t in
the time domain by at , we must replace the variable ω in the frequency domain by ω ⁄ a , and
divide F ( ω ⁄ a ) by the absolute value of a .
Proof:
We must consider both cases a > 0 and a < 0 .
For a > 0 ,
∞
– jωt
F { f ( at ) } = ∫–∞ f ( at )e dt (8.41)
τ ω
∞ – jω ⎛ --- ⎞ ∞ – j ⎛ ----⎞ τ
⎝a⎠ τ ⎝ a⎠ 1 ω
d ⎛ --- ⎞ = --- dτ = --- F ⎛ ----⎞
1
F {f(τ)} = ∫–∞ f ( τ )e ⎝ a⎠ a ∫–∞ f ( τ )e a ⎝ a⎠
For a < 0 ,
∞
– jωt
F { f ( –at ) } = ∫–∞ f ( –at )e dt
and making the above substitutions, we find that the multiplying factor is – 1 ⁄ a . Therefore, for
1 ⁄ a we obtain (8.40).
4. Time Shifting
If F ( ω ) is the Fourier transform of f ( t ) , then,
– jωt 0
f ( t – t 0 ) ⇔ F ( ω )e (8.42)
that is, the time shifting property of the Fourier transform states that if we shift the time function
f ( t ) by a constant t 0 , the Fourier transform magnitude does not change, but the term ωt 0 is
added to its phase angle.
Proof:
∞
– jωt
F { f ( t – t0 ) } = ∫–∞ f ( t – t )e 0 dt
or
– jωt 0
F { f ( t – t0 ) } = e F(ω)
5. Frequency Shifting
If F ( ω ) is the Fourier transform of f ( t ) , then,
jω 0 t
e f ( t ) ⇔ F ( ω – ω0 ) (8.43)
jω 0 t
that is, multiplication of the time function f ( t ) by e , where ω 0 is a constant, results in shifting
the Fourier transform by ω 0 .
Proof:
∞
F { e jω t f ( t ) }0
= ∫– ∞ e
jω 0 t
f ( t )e
– jωt
dt
or
jω 0 t ∞ –j ( ω – ω0 )
F {e f(t)} = ∫–∞ f ( t )e dt = F ( ω – ω 0 )
ω–ω
f ( at ) ⇔ ----- F ⎛ ----------------0 ⎞
jω 0 t 1
e
⎝ ⎠
(8.44)
a a
Property 5, that is, (8.43) is also used to derive the Fourier transform of the modulated signals
f ( t ) cos ωt and f ( t ) sin ωt . Thus, from
jω 0 t
e f ( t ) ⇔ F ( ω – ω0 )
and
jω 0 t –j ω0 t
e +e
cos ω 0 t = -------------------------------
2
we get
F ( ω – ω0 ) + F ( ω + ω0 )
f ( t ) cos ω 0 t ⇔ ----------------------------------------------------------
- (8.45)
2
Similarly,
F ( ω – ω0 ) –F ( ω + ω0 )
f ( t ) sin ω 0 t ⇔ -------------------------------------------------------
- (8.46)
j2
6. Time Differentiation
If F ( ω ) is the Fourier transform of f ( t ) , then,
n
d
-------- f ( t ) ⇔ ( jω ) n F ( ω ) (8.47)
n
dt
n
d n
that is, the Fourier transform of -------n- f ( t ) , if it exists, is ( jω ) F ( ω ) .
dt
Proof:
Differentiating the Inverse Fourier transform, we get
∞ ∞
n – j ωt – j ωt
∫– ∞ ∫–∞ f ( t )e
n
= f ( t ) ( –j t ) e dt = ( – j t ) dt
Proof:
We postpone the proof of this property until we derive the Fourier transform of the unit step
function u 0 ( t ) on the next section. In the special case where in (8.49), F ( 0 ) = 0 , then,
t
F(ω)
∫–∞ f ( τ ) dτ ⇔ ------------
jω
(8.50)
and this is easily proved by integrating both sides of the Inverse Fourier transform.
9. Conjugate Time and Frequency Functions
If F ( ω ) is the Fourier transform of the complex function f ( t ) , then,
f∗ ( t ) ⇔ F ∗ ( – ω ) (8.51)
Proof:
∞ ∞
– jωt – jωt
F(ω) = ∫– ∞ f ( t )e dt = ∫–∞ [ fRe ( t ) + jfIm ( t ) ]e dt
∞ ∞
– jωt – jωt
= ∫– ∞ f Re ( t )e dt + j ∫–∞ fIm ( t )e dt
Then,
∞ ∞
F∗ ( ω ) = ∫– ∞ ∫–∞ fIm ( t )e
jωt jωt
f Re ( t )e dt – j dt
f 1 ( t )∗ f 2 ( t ) ⇔ F 1 ( ω )F 2 ( ω ) (8.52)
that is, convolution in the time domain, corresponds to multiplication in the frequency domain.
Proof:
∞ ∞
– jωt
F { f1 ( t )∗ f2 ( t ) } = ∫–∞ ∫–∞ f ( τ )f2 ( t – τ ) dτ
1 e dt
(8.53)
∞ ∞
– jωt
= ∫–∞ f ( τ ) ∫–∞ f ( t – τ )e
1 2 dt dτ
The first integral above is F 1 ( ω ) while the second is F 2 ( ω ) , and thus (8.52) follows.
Alternate Proof:
– jωt 0
We can apply the time shifting property f ( t – t 0 ) ⇔ F ( ω )e into the bracketed integral of
– jωt 0
(8.53); then, replacing it with F 2 ( ω )e , we get
∞ ∞ ∞ – jωt 0
– jωt
F { f 1 ( t )∗ f 2 ( t ) } = ∫– ∞ f1 ( τ ) ∫– ∞ f 2 ( t – τ )e dt dτ = ∫–∞ f ( τ ) dτF
1 2 ( ω )e
∞
– jωt
= ∫–∞ f ( τ )e
1 dτF 2 ( ω ) = F 1 ( ω )F 2 ( ω )
1
f 1 ( t )f 2 ( t ) ⇔ ------ F 1 ( ω )∗ F 2 ( ω ) (8.54)
2π
that is, multiplication in the time domain, corresponds to convolution in the frequency domain
divided by the constant 1 ⁄ 2π .
Proof:
∞ ∞ ∞
– jωt 1- – jωt
∫– ∞ ∫ ∫–∞ F ( χ )e
jχt
F { f1 ( t )f2 ( t ) } = [ f 1 ( t ) f 2 ( t ) ]e dt = -----
2π 1 dχ f 2 ( t )e dt
–∞
∞ ∞ ∞
1 – j ( ω – χ )t 1
= ------
2π ∫– ∞ F1 ( χ ) ∫– ∞ f 2 ( t )e dt dχ = ------
2π ∫–∞ F ( χ )F ( ω – χ ) dχ
1 2
that is, the area under a time function f ( t ) is equal to the value of its Fourier transform evaluated
at ω = 0 .
Proof:
– jωt
Using the definition of F ( ω ) and that e ω=0
= 1 , we see that (8.55) follows.
that is, the value of the time function f ( t ) , evaluated at t = 0 , is equal to the area under its Fou-
rier transform F ( ω ) times 1 ⁄ 2π .
Proof:
jωt
In the Inverse Fourier transform of (8.3), we let e t=0
= 1 , and (8.56) follows.
that is, if the time function f ( t ) represents the voltage across, or the current through an 1 Ω resis-
tor, the instantaneous power absorbed by this resistor is either v 2 ⁄ R , v 2 ⁄ 1 , v 2 , or i 2 R , i 2 . Then,
the integral of the magnitude squared, represents the energy (in watt-seconds or joules) dissipated
by the resistor. For this reason, the integral is called the energy of the signal. Relation (8.57) then,
states that if we do not know the energy of a time function f ( t ) , but we know the Fourier trans-
form of this function, we can compute the energy without the need to evaluate the Inverse Fou-
rier transform.
Proof:
From the frequency convolution property,
1
f 1 ( t )f 2 ( t ) ⇔ ------ F 1 ( ω )∗ F 2 ( ω )
2π
or
∞ ∞
– jωt 1
F { f1 ( t )f2 ( t ) } = ∫– ∞ [ f 1 ( t )f 2 ( t ) ]e dt = ------
2π ∫–∞ F ( χ )F ( ω – χ ) dχ
1 2 (8.58)
Since (8.58) must hold for all values of ω , it must also be true for ω = 0 , and under this condi-
tion, it reduces to
∞ ∞
1
∫ –∞
[ f 1 ( t )f 2 ( t ) ] dt = ------
2π ∫–∞ F ( χ )F ( –χ ) dχ
1 2 (8.59)
For the special case where f 2 ( t ) = f 1∗ ( t ) , and the conjugate functions property f∗ ( t ) ⇔ F∗ ( – ω ) ,
by substitution into (8.59), we get:
∞ ∞ ∞
1 1
∫ –∞
[ f ( t )f∗ ( t ) ] dt = ------
2π ∫ –∞
F ( ω )F∗ [ – ( – ω ) ] dω = ------
2π ∫–∞ F ( ω )F∗ ( ω ) dω
Since f ( t )f∗ ( t ) = f ( t ) and F ( ω )F∗ ( ω ) = F ( ω ) , Parseval’s theorem is proved.
2 2
The Fourier transform properties and theorems are summarized in Table 8.8.
∫–∞ f ( t )δ ( t – t ) dt
0 = f ( t0 )
∫–∞ f ( t )δ ( t ) dt = f( 0)
0 t 0 ω
Property f( t) F(ω)
Linearity a1 f1 ( t ) + a2 f2 ( t ) + … a1 F1 ( ω ) + a2 F2 ( ω ) + …
Symmetry F(t) 2πf ( – ω )
Time Scaling f ( at ) ω
----- F ⎛ ----⎞
1
a ⎝ a⎠
Time Shifting f ( t – t0 ) – jωt 0
F ( ω )e
Frequency Shifting jω 0 t F ( ω – ω0 )
e f(t)
Time Differentiation n n
d ( jω ) F ( ω )
--------- f ( t )
n
dt
Frequency Differentiation n n
( – jt ) f ( t ) d
----------- F ( ω )
n
dω
Time Integration t F ( ω ) + πF ( 0 )δ ( ω )
∫– ∞
------------
f ( τ ) dτ jω
Conjugate Functions f∗ ( t ) F∗ ( – ω )
Time Convolution f 1 ( t )∗ f 2 ( t ) F1 ( ω ) ⋅ F2 ( ω )
Frequency Convolution f1 ( t ) ⋅ f2 ( t ) 1
------ F 1 ( ω )∗ F 2 ( ω )
2π
Area under f(t) ∞
F(0) = ∫–∞ f ( t ) dt
Area under F(w) ∞
∫
1
f ( 0 ) = ------ F ( ω ) dω
2π – ∞
Parseval’s Theorem ∞ ∞
∫ ∫
2 1 2
f ( t ) dt = ------ F ( ω ) dω
–∞ 2π –∞
– jωt 0
δ ( t – t0 ) ⇔ e (8.61)
2.
1 ⇔ 2πδ ( ω ) (8.62)
Proof:
–1 ∞ ∞
1
∫– ∞ ∫–∞ δ ( ω )e
jωt jωt jωt
F { 2πδ ( ω ) } = ------ 2πδ ( ω )e dω = dω = e ω=0
= 1
2π
f(t) F(ω)
1
2πδ ( ω )
0 t 0 ω
Also, by direct application of the Inverse Fourier transform, or the frequency shifting property
and (8.62), we derive the transform
jω 0 t
e ⇔ 2πδ ( ω – ω 0 ) (8.63)
The transform pairs of (8.62) and (8.63) can also be derived from (8.60) and (8.61) by using the
symmetry property F ( t ) ⇔ 2πf ( – ω )
3.
1 jω 0 t –j ω0 t
cos ω 0 t = --- ( e +e ) ⇔ πδ ( ω – ω 0 ) + πδ ( ω + ω 0 ) (8.64)
2
Proof:
This transform pair follows directly from (8.63). The f ( t ) ↔ F ( ω ) correspondence is also shown
in Figure 8.3.
cosωω
cos 0 t0
t F Re ( ω )
π π
t t
−ω0 0 ω0 ω
We know that cos ω 0 t is real and even function of time, and we found out that its Fourier trans-
form is a real and even function of frequency. This is consistent with the result in Table 8.7.
4.
1 jω0 t –j ω0 t
sin ω 0 t = ----- ( e –e ) ⇔ jπδ ( ω – ω 0 ) – jπ δ ( ω + ω 0 ) (8.65)
j2
Proof:
This transform pair also follows directly from (8.63). The f ( t ) ↔ F ( ω ) correspondence is also
shown in Figure 8.4.
sin ω 0 t F Im ( ω )
π
tt −ω0
0 ω0 ω
−π
We know that sin ω 0 t is real and odd function of time, and we found out that its Fourier trans-
form is an imaginary and odd function of frequency. This is consistent with the result in Table
8.7.
5.
2
sgn ( t ) = u 0 ( t ) – u 0 ( – t ) ⇔ ------ (8.66)
jω
−1
f(t)
1
– at
e u0 ( t )
0
– at −1
–e u0 ( –t )
Then,
– at at
sgn ( t ) = lim [ e u0 ( t ) – e u0 ( –t ) ] (8.67)
a→0
and
0 ∞
at – j ωt – a t – j ωt
F { sgn ( t ) } = lim
a→0 ∫– ∞ –e e dt + ∫0 e e dt
0 ∞
( a – j ω )t – ( a + jω ) t
= lim
a→0 ∫– ∞ –e dt + ∫0 e dt (8.68)
1 1 –1 1 2
= lim --------------- + --------------- = --------- + ------ = ------
a→0 a – jω a + jω – jω jω jω
f( t)
F Im ( ω )
1
0
t ω
0
−1